Study of linguistic attitudes in quechua-spanish bilinguals from the district of San Juan de Lurigancho towards the quechua language - Ytusaca Quispe, Claudia Adela (2022)
José Carlos Mariátegui, a human settlement in the district of San Juan de Lurigancho (Lima, Peru), is a community where people living and interacting with different cultures, including bilingual inhabitants of spanish and quechua. This context allows us to show the relationship between language and society through the linguistic attitudes of its inhabitants. In this sense, the present study is an approach to the description of the linguistic attitudes of a group of bilingual Andean migrants (quechua-castilian) towards their mother tongue, quechua, versus castilian. From the perspective of mentalist theory and its dimensions: conative, cognitive and affective, as well as, the application of a questionnaire and a sociolinguistic interview, the perception of bilingual mariateguin adults towards their mother tongue was analyzed. The results showed the positive assessment towards quechua, mainly from the affective dimension.